Depiction of a seated Vishnu with four arms - Temples of India Project Team (Jio Institute, 2024)
One of the bhadras (central offsets) of the garbhagriha (sanctum sanctorum) of the Undeshwar Temple features a seated Vishnu depicted with four arms. Adorned with a crown, Vishnu holds a gada (mace) and a chakra (discus) in his upper hands. In his lower right hand, he holds an akshamala (rosary) while also displaying the Varada hasta (hand gesture of conferring a boon) gesture. Unfortunately, his lower left hand is damaged. The figure is adorned with elaborate jewelry including large circular earrings, a broad beaded necklace, a breast band, a girdle, bangles and anklets.